MEASUREMENT OF WATER DISCHARGE OF SAKARTEMEN RIVER TO IDENTIFY POTENTIAL OF MICRO HYDRO POWER PLANT IN FAKFAK REGENCY - Yulianto La Elo; Zharin Fahra Syahdinar; Febriyan Febriyan; Rafa Alaudin Keliolan (Jurusan Pendidikan Teknik Elektro, 2024)
Fakfak Regency, West Papua Province is one of the oldest regencies in Papua. However, electricity problems are still a scourge that has not yet been resolved properly. So far, the mainstay of power plants in Fakfak Regency is the Diesel Power Plant (PLTD) which is highly dependent on the supply of Fuel Oil (BBM) and the reliability of the Diesel Engine. In fact, Fuel Oil (BBM) is one of the natural resources that cannot be renewed. For this reason, it is necessary to conduct a study on New Renewable Energy (EBT) that has the potential to be developed in Fakfak Regency. There are several rivers that have the potential to be developed as Micro Hydro Power Plants (PLTMH) in Fakfak Regency. The existence of Micro Hydro Power Plants (PLTMH) in Fakfak Regency is one of the real solutions to the power outages that still often occur in Fakfak Regency. Through this study, it is hoped that there will be a mapping of the energy potential that can be produced by several rivers in Fakfak Regency if used as Micro Hydro Power Plants (PLTMH). In addition, the potential of Micro Hydro Power Plant (PLTMH) will support the transition of power plants in Fakfak Regency. Another objective is to support environmental conservation efforts (nature and culture) and increase community participation in the management of existing natural resources, thus providing economic benefits to the local community. The research was conducted through surveys and direct measurements where the measurement results will be calculated to determine the potential river flow discharge and the potential for power generation. The results of the measurements and calculations obtained an average discharge of the Sakartemen River of 3.1m3/second which based on the measurement of the effective fall height (Heff) of the flow was obtained at 4 m. With these results, it can be estimated that the electrical power generated is 104,260 kW.